2013
DOI: 10.1155/2013/801374
|View full text |Cite
|
Sign up to set email alerts
|

A New Type of Biphasic Calcium Phosphate Cement as a Gentamicin Carrier for Osteomyelitis

Abstract: Osteomyelitis therapy is a long-term and inconvenient procedure for a patient. Antibiotic-loaded bone cements are both a complementary and alternative treatment option to intravenous antibiotic therapy for the treatment of osteomyelitis. In the current study, the biphasic calcium phosphate cement (CPC), called α-TCP/HAP (α-tricalcium phosphate/hydroxyapatite) biphasic cement, was prepared as an antibiotics carrier for osteomyelitis. The developed biphasic cement with a microstructure of α-TCP surrounding the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…A n area gaining increasing interest for treating bone and soft tissue infections is the controlled release and local delivery of antibiotics from suitable carriers [1][2][3][4][5][6]. The benefits of ''local release'' are substantial and include the ability to provide high local concentrations of antibiotic, many times the minimum inhibitory concentration (MIC) [7], with serum concentrations and associated toxicity remaining low [8][9][10].…”
mentioning
confidence: 99%
“…A n area gaining increasing interest for treating bone and soft tissue infections is the controlled release and local delivery of antibiotics from suitable carriers [1][2][3][4][5][6]. The benefits of ''local release'' are substantial and include the ability to provide high local concentrations of antibiotic, many times the minimum inhibitory concentration (MIC) [7], with serum concentrations and associated toxicity remaining low [8][9][10].…”
mentioning
confidence: 99%
“…The superiority of CGS over PMMA beads has been proven in clinical and animal studies 15 , 16 , 17 . Also calcium phosphate cements have proved to be a viable carrier of local antimicrobial agent allowing prolonged release of gentamicin sulfate or tobramicin 18 , 19 . Depending on the extend of the infection within calcaneus and presence of skin defect, the spectrum of surgical procedures includes partial or total calcanectomy and lower leg amputation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the potential of bioceramics as a depot for antibiotic delivery. 15,16,[18][19][20][21][22][23] However, bioceramics have significantly weaker mechanical properties than PMMA, preventing their use in loadbearing implants, such as knee and hip spacers. Overall, current treatment options lack both the mechanical strength and elution kinetics to effectively treat bone infections while bearing highmechanical loads.…”
Section: Periprosthetic Joint Infection (Pji) Is An Infection Most Cmentioning
confidence: 99%